Determination of apomixis by flow cytometry in two species of Lachemilla (Rosaceae) in Ecuador. Issue 1 (30th November 2018) - Samaniego, Fernanda; Kolár, Filip; Urfus, Tomas; Barragán, Álvaro; Romoleroux, Katya
ABSTRACT: The genus Lachemilla in Ecuador consists of 27 species distributed along the páramos and superpáramos of the Andes. With 11 species, it is one of the most species-rich genera in the superpáramo zone. We report the presence of apomixis in Lachemilla hirta and L. hispidula . Both species were regularly visited by entomofauna, where Diptera were the most representative group. Three treatments (enclosing the inflorescences with mesh bags, wax paper bags and the open-pollinated control) were used to determine the presence of pollination, apomixis and both processes respectively. In the fruiting assays with the mesh bags, L. hirta showed no significant differences when compared to the control treatments; whereas highly significant differences between treatments were found in L. hispidula, where the control treatment was the treatment with more fruit production, which according to the apomixis results, could mean and accidental pollination activity from the insects found in this study. The flow cytometric screen of seeds from all three treatments showed that these species are predominantly autonomous apomicts. Additionally, pseudogamous seeds in L. hirta, and triploid embryos in L. hispidula were also found though in smaller quantities. Interestingly, these results indicate Lachemilla as the very first case of documented apomixis from the páramo ecosystem. Our results suggest that populations of both species are asexual. Furthermore, insects found on these plants use them strictly as feeding sites, for protection and for reproduction, and rarely act as accidental pollinators.